Coupled Mg/Ca and clumped isotope analyses of foraminifera provide consistent water temperatures - Breitenbach, Sebastian F.M.; Mleneck-Vautravers, Maryline J.; Grauel, Anna Lena; Lo, Li; Bernasconi, Stefano M.; Müller, Inigo A.; Rolfe, James; Gázquez, Fernando; Greaves, Mervyn; Hodell, David A. (Geochimica et Cosmochimica Acta, 2018)
The reliable determination of past seawater temperature is fundamental to paleoclimate studies. We test the robustness of two paleotemperature proxies by combining Mg/Ca and clumped isotopes (Δ 47 ) on the same specimens of core top planktonic foraminifera. The strength of this approach is that Mg/Ca and Δ 47 are measured on the same specimens of foraminifera, thereby providing two independent estimates of temperature. This replication constitutes a rigorous test of individual methods with the advantage that the same approach can be applied to fossil specimens. Aliquots for Mg/Ca and clumped analyses are treated in the same manner following a modified cleaning procedure of foraminifera for trace element and isotopic analyses. We analysed eight species of planktonic foraminifera from coretop samples over a wide range of temperatures from 2 to 29°C. We provide a new clumped isotope temperature calibrations using subaqueous cave carbonates, which is consistent with recent studies. Tandem Mg/Ca–Δ 47 results follow an exponential curve as predicted by temperature calibration equations. Observed deviations from the predicted Mg/Ca-Δ 47 relationship are attributed to the effects of Fe-Mn oxide coatings, contamination, or dissolution of foraminiferal tests. This coupled approach provides a high degree of confidence in temperature estimates when Mg/Ca and Δ 47 yield concordant results, and can be used to infer the past δ 18 O of seawater (δ 18 O sw ) for paleoclimate studies.